THE EXISTENCE OF ALBASIA PLANTS IN CIKARAMAS VILLAGE: A CASE STUDY OF ALBASIA CULTIVATION IN CIKARAMAS VILLAGE, SUMEDANG REGENCY, WEST JAVA - Hamda Khairuzani (Journal of Science Innovare, 2022)
With forestry development, it is hoped that national development goals will be achieved, in particular the improvement of living standards and community welfare accompanied by improvement of their living environment. Wood is one of the main forest products, which is needed by the community to meet various needs of human life. Although nowadays there are many synthetic materials that can substitute the use of wood, the demand for wood for various purposes is still quite high and even shows an increasing demand. The benefits of this wood are growing, starting from the need for wood for energy, building materials, wood pulp, furniture, to the use of wood for aircraft fuselages. The planting of sengon trees by the community in Cikaramas Village is quite developed and is very suitable considering the topography and land conditions that are suitable for the place where sengon trees grow. Then it becomes a separate added value, if farmers/communities are able to optimize inputs for forest plant cultivation by knowing in advance the characteristics/characteristics of the soil. Albasia that developed in Cikaramas Village, is part of the knowledge system of Cikaramas Village residents about timber plants. The system is a legacy of knowledge about the types and uses of woody plants for subsistence needs used for building materials. Prior to the development of albasia, wood plants of the type of tissue, jackfruit wood, and the type of "swamp" wood had been developed and used for the needs of previous building materials. Then the development of albasia plant species, causing choices in developing woody plants to be utilized and to be developed in more intercropping systems. This allows farmers to choose based on their knowledge and experience, and choose based on the benefits and advantages derived from the timber plant, which will be developed in an intercropping system. This study uses descriptive qualitative research, researchers try to get a picture of the ongoing state of the object of research according to the actual situation, so that accurate data can be obtained with an actual picture from the analysis of the observed phenomena. Through this research, it is hoped that data will be obtained and presented through the use of words to obtain a more concrete, detailed and accurate description of certain phenomena.  The development and use of Albasia in Cikaramas Village is a form of adaptation carried out by the community that responds to environmental suitability and changes. Response to information or ideas that enter the social system of Cikaramas Village, which has an influence on the ecological system of Cikaramas Village. And the socio-economic activities of Albasia gave birth to the Albasia trading network. As well as the survival of Albizia as a commodity crop under the influence of the threat of crop failure due to pests, factored in by economic sector and ecological sector.